Kapasitas Petani Padi Sawah Dalam Mendukung Ketahanan Pangan Keluarga Berkelanjutan Di Kabupaten Pandeglang - Sri Mulyati; Khaerul Saleh; Asih Mulyaningsih (JURNAL AGRIBISNIS TERPADU, 2020)
This study aims to analyze the level of farmer capacity in managing lowland rice farming in Pandeglang district and the determinants that can influence the capacity building of lowland rice farmers in supporting family food security in Pandeglanag Regency. The population in this study were lowland rice farmers who were in the research location. The research location was in three districts, namely Munjul, Sobang and Panimbang districts. The research design used qualitative and quantitative approaches involving 144 respondents representing three districts, the data collected were primary data and secondary data. Primary data were collected through interviews using questionnaires, in-depth interviews, observation and documentation study. The data consists of the characteristics of the respondent (ξ1); Technological innovation (ξ2); Extension activities (ξ3); Capacity (η1); and Family food safety (η2). The selection of respondents was carried out by proportional random sampling (proportionally random sampling) based on the research criteria. Data analysis used descriptive statistics, one way ANOVA and Structural Equation Modeling (SEM). The results showed that the capacity of lowland rice farmers was in the medium category. The element that most influenced the capacity level was the respondent's characteristic of 0.81 (76.25 percent) through land tenure and farming experience. Meanwhile, extension activities only contributed 0.07 (2.3 percent) through indicators of extension methods and intensity. Meanwhile, technological innovation still has a negative effect on the capacity of farmers in increasing family food security. In general, the capacity of lowland rice farmers has high support for family food security, especially in indicators of consumption levels and food sustainability.